A new species of dink frog, genus Diasporus (Anura: Eleutherodactylidae), from the Caribbean foothills of the Cordillera de Talamanca, Costa Rica - Arias, Erick; Chaves, Gerardo; Salazar, Stanley; Salazar-Zúñiga, José Andrés; García-Rodríguez, Adrián (Zootaxa, 2019)
A new dink frog (Eleutherodactylidae: Diasporus) is described from the Tropical Wet Forest, in the northeastern foothills of Cordillera de Talamanca in Costa Rica at an elevation of ca. 1000 m. Analysis of DNA sequences of the 16S rRNA (16S) and cytochrome oxidase 1 (COI) mitochondrial genes revealed a distinct lineage within the genus Diasporus. Additional morphological, morphometric, and acoustic analyses support the differences of this lineage, which we recognize as a new species. This new taxon is distinguished from other members of the genus Diasporus inhabiting Isthmian Central America by its unique coloration: dorsum brown to brown-grayish and venter gray-bluish with pale blotches. The new species is distinguished from other members of the genus Diasporus by very significant genetic distances (higher than 5.6 % in 16S and 16.7 % in COI). The new taxon is most closely related to D. vocator from the south pacific of Costa Rica and to an unnamed taxon from western Panama.